The Vindictive and Contestatory Heterotopias in Adriana Bustos’ Photography Production - Hidalgo Redondo, Giselle (2021)
This article is centered in the social criticism done by the Argentinian contemporary artist Adriana Bustos. Particularly, on the socioeconomic exploitation that Latin America has suffered since colony. Her visual texts show hidden relationships between events and dissimilar times. This time-space divergence is shown through her artistic heterotopic, which displays her world view within a framework of images and texts, designated by Bustos as her non-lineal version of history. The exploration of her artistic work will be focused on the theoretical approach found in Michel Foucault’s heterotopic.